DEVELOPMENT OF CHARACTER VALUE-BASED EDUCATION GAMES FOR ELEMENTARY SCHOOL (SD) STUDENTS - Yulianti, Yulianti; Rahayu, Marta Indah; Sulistyowati, Prihatin (International Research-Based Education Journal, 2022)
This study aims to determine the feasibility, practicality and effectiveness of the educational game "Warrior Adventure" based on the nationalist character of the struggle for Indonesian independence for elementary school students in grade V. This study uses the ADDIE development model with five stages, namely analysis, design, development, implementation, and evaluation. The data collection instrument used was a questionnaire. The subjects of this research trial were students of class V SDN Tempurejo 02 totaling 12 students. Material expert validation obtained a percentage of 94% categorized as very feasible, 97% linguistic experts categorized as very feasible, 96% media experts categorized as very feasible. The teacher's practicality test obtained a percentage of 93% categorized as very good, and students' practicality 92.5% categorized as very good. The effectiveness test of students obtained an average score of 88 which was categorized as very effective. Based on the research data, it was concluded that the educational game "Warrior Adventure" based on nationalist characters was declared feasible, practical and effective to be used as a learning medium in supporting the learning process.